Tendencies of development of youth extremism in the conditions of progress of information and computer technologies - E. O. Kubyakin (Vestnik MGIMO-Universiteta)
Society is modern is characterized by promptly increasing information streams. As a result of development of the Internet, increase of speed of transmission of messages traditional means and ways of the analysis of character, a context, an orientation of messages lose the importance. One of the negative phenomena in Russia is today an extremism who in modern conditions is integrated into an Internet environment. Effektvnoye counteraction to this phenomenon, in the near future, will consist in improvement of software of the Internet monitoring allowing in real time to carry out the computer content analysis, the linguistic analysis of text streams containing various materials of a global network, including the extremist.